PENDAMPINGAN PENYUSUNAN ANGGARAN BIAYA PRODUKSI EMPING MELINJO PADA USAHA EMPING BU-MULYATI DI KOTA SERANG - Sukirno, Sukirno; Huddin, Muhammad Nurhaula (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
This community service program aims to improve the ability of the owner of “Emping Bu-Mulyati” microenterprise to prepare and use a production cost budget as a tool for cost control and for setting a more rational selling price of melinjo chips. The program was motivated by the absence of proper financial records, cost of goods manufactured that was still based on rough estimates, and the mixture of business and household finances which made it difficult to measure profit accurately. The method used was a participatory mentoring approach through several stages, namely initial survey and diagnosis, training on production cost classification and budget format, hands-on practice in preparing multi-stage production cost budgets, analysis and decision-making simulations, as well as evaluation and sustainability commitment. The results indicate an improvement in the partner’s understanding of production cost structure (materials, labour, and overhead), the completion of a set of melinjo chips production cost budget documents per period, the ability to calculate unit cost of goods more systematically, and the emergence of new habits in recording cash inflows and outflows and separating business from personal finances. This mentoring program is expected to strengthen the competitiveness of Emping Bu-Mulyati through better cost control and data-based pricing